The pesticide dichlorvos disrupts mitotic division by delocalizing the kinesin Kif2a from centrosomes. (26th March 2013) - Fiore, Mario; Mattiuzzo, Marta; Mancuso, Graziella; Totta, Pierangela; Degrassi, Francesca
<x xml:space="preserve">Abstract</x> The molecular mechanism(s) mediating long‐term adverse effects of dichlorvos, a widely used insecticide, are still unclear. Our work uncovered a new cellular effect of dichlorvos in cultured human cells, i.e. its capacity to induce extremely aberrant mitotic spindles with monopolar microtubule arrays that were associated with hypercondensed chromosomes and pyknotic chromatin masses. Monopolar spindles produced by dichlorvos treatment were characterized by the delocalization of the depolymerizing kinesin Kif2a from spindle poles. Dichlorvos‐induced spindle monopolarity could be reversed by promoting microtubule stabilization through chemical treatment or by inhibiting the depolymerizing function of the kinesin MCAK at kinetochores. These findings demonstrate that dichlorvos inhibits the depolymerizing activity of Kif2a at centrosomes and thereby disrupts the balance of opposing centrosomal and kinetochore forces controlling spindle bipolarity during prometaphase. Dichlorvos‐induced defects in spindle bipolarity may be responsible for the previously reported induction of aneuploidy by this chemical. Collectively, these results indicate that environmental chemicals, such as dichlorvos, may promote chromosome instability by interfering with the cell division machinery. Environ. Mol. Mutagen. 54:250–260, 2013. © 2013 Wiley Periodicals, Inc.